Validation of Stability-Indicating RP-HPLC Method and Determination of Impurities by LC-QTOF-MS for Adenosine in Eye Drops - Caliskan, Cem; Koyuncu, Ikbal (OXFORD UNIV PRESS INC, 2022)
Background Presently, there is no validated method for stability-indicating related substances of adenosine used in the treatment of cataracts and found in different combined eye drop products. Objective A stability-indicating related substances analytical method for adenosine used in the treatment of cataracts and found in different combined eye drop products should be developed and validated. Method A new reverse phase-HPLC method of determination for adenosine-related compounds has been developed and validated according to the International Council for Harmonisation. In this method, all impurities were easily detected for adenosine, which is found in combination with different active ingredients such as nicotinic acid and nicotinamide. The impurities obtained by a stress test were purified and their structures were characterized by mass spectroscopy (LC-QTOF-MS). Results The concentration range for linearity was evaluated as 0.06-4.27 mu g/mL for adenosine, 0.15-4.27 mu g/mL for uridine, 0.15-4.17 mu g/mL for inosine, 0.13-4.35 mu g/mL for guanosine, and 0.12-4.26 mu g/mL for adenine. Good linearity was achieved for each component, and it was determined that the correlation coefficient (r) met the acceptance criterion r >= 0.99. The accuracy of the method was good-to-excellent recoveries at each concentration level (from LOQ to 120% of the specification limit) were achieved within the limit range of 80.0-120.0%, and RSD of recoveries was found below 10.0% for both formulations. Conclusions With this economical and simple method validated in accordance with the ICH Q2 (R1) guideline, a new method has been created for adenosine, which is suitable for routine analysis.
Keywords: Chemistry; Food Science & Technology